Interferensi Leksikal Bahasa Inggris dalam Pemakaian Bahasa Indonesia Karyawan Pariwisata - Karmaningsih, Desak Putu; Arnati, Ni Wayan (Humanis; Vol 23 No 3 (2019)DO - 10.24843/JH.2019.v23.i03.p04, 2019)
The research is entitled “ Lexical Interference in English in Use of Indonesian Language in Tourism Employees in Ubud Subdistrict ” . The purpose of this study was to analyze the form of lexical interference and the factors that cause interference exical English in the use of Indonesian language tourism employees in the District of Ubud.the theory used is the theory of sociolinguistic by Jendra. To achieve these objectives, several methods and technique are used. The source of the data for analysis was the employee tourism conversations in Ubud District with a total of 50 employees. The results of this study are there are lexical forms at the level of words and interference at the level of phrases, categories of words such as nouns, adjectives, and verbs, factors that cause interference such as informants' bilingualism, habit factors that are influenced by the profession, factors in their own language, familiarity factors.